Satisfaction of patients to dental care received in a hospital in Lima - Lara-Alvarez, Jefferson Jonathan (2020)
Objective: To determine the satisfaction of patients who received a dental service in a hospital in Lima. Mate- rial and methods: The study was observational, cross-sectional and descriptive. The sample consisted of 702 patients. The modified SERVQUAL instrument was used to determine patient satisfaction. Patients older than or equal to 18 years of age with the right to be treated who attended the dental area were included. Results: The frequency of dissatisfied patients was 88.6%, being 622 of 702 (p = 0.000). Dissatisfaction was greater in pa- tients aged between 35-49 years with 34.5% and in patients who went to diagnosis with 30.9%; being statistically significant in these cases. Conclusions: Most patients who received care in the dental service were dissatisfied with the care.